Backscatter amplification effect in a non-Kolmogorov anisotropic turbulent medium. (October 2022) - Banakh, V.A.; Falits, A.V.
Highlights: Backscatter amplification effect in non-Kolmogorov anisotropic turbulence is studied for the first time. It is shown that the amplification factor depends on the exponent of the turbulence spectrum. It increases by 1.3 times with increasing the spectrum exponent from 3.05 to 3.89. Anisotropy of turbulence leads to decrease of the amplification factor. Abstract: The paper presents a tool for numerical simulation of the backscatter amplification effect associated with double-pass propagation of laser radiation passing through an anisotropic non-Kolmogorov turbulence. It is shown that for variety of power-law exponents of refractive-index fluctuations, all other conditions being equal, the value of amplification factor also changes: the amplification factor increases when the fluctuation spectrum becomes more and more low-frequency. For the anisotropic medium, the two-dimensional distribution of the amplification factor allows remotely determining the spatial orientation of anisotropic inhomogeneities in a randomly inhomogeneous medium.